Reality TV and reality show: fiction and reality on television - Rocha, Debora Cristine (2010)
Reality TV, a variety of popular factual programming, influences numerous televised formats. Although the format more associated with this type of television is the reality show, it is not restricted to it, its styles and techniques are transferred to TV in general, aiming to make its texts even more realistic. Simulation plays an important role, as a language process which makes the lived world – a natural world represented by signs –, a communication system, that feeds the media world – the universe created by the representation. In this process communication dialogues with ethnography: ethnographic data are translated from the lived world into the media world, as veracity and credibility indicators. Both reality TV and reality shows make use of ethnography to fulfill the promise to exhibit the maximum of reality. However, fiction subsists on the inside of both.